Using Haptic Feedback as a Treatment for Position Dependent, Severe, Chronic Snoring. (November 2019) - Murph, Imani A.; French, John; Kukuvka, Matt; Bush, Dylan
Severe snoring reduces sleep duration, sleep quality and has been linked to severe daytime fatigue, obesity and possibly sleep apnea and cardiovascular disease. Most snoring is position dependent and most prominent while sleeping on one's back. The haptic sleep device (HSD) prevents sleeping on the back by using vibrating disks, which are activated until the sleeper rotates off the back. We monitored four heavy snorers, six moderate to light snorers, and four non-snorers. Our results show that wearing the HSD was associated with a reduction in sleeping on the back, a longer duration of sleep, and a reduction in restlessness during sleep. The HSD is designed to train a person, over time, to sleep on their side. These data indicate that the HSD is an effective anti-snoring device and could lead to other health benefits for the user.